Modelling the relationship between environmental factors, transcriptional genes and deoxynivalenol mycotoxin production by strains of two Fusarium species - Schmidt-Heydt, Markus; Parra-Saldívar, Roberto; Geisen, Rolf; Magan, Naresh (Cranfield University, 2011)
The effect of changes in temperature/water activity (a(w)) on growth, deoxynivalenol (DON) production and trichothecene gene cluster expression (18 genes) for strains of Fusarium culmorum and Fusarium graminearum was studied. The expression data for six key transcription genes (TRI4, TRI5, TRI6, TRI10, TRI12 and TRI13) were analysed using multiple regression analyses to model the relationship between these various factors for the first time. Changes in a(w) and temperature significantly (p=0.05) affected growth and DON. Microarray data on expression of these genes were significantly related to DON production for both strains. Multi-regression analysis was done and polynomial models found to best fit the relationship between actual/predicted DON production relative to the expression of these TRI genes and environmental factors. This allowed prediction of the amounts of DON produced in two-dimensional contour maps to relate expression of these genes to either a(w) or temperature. These results suggest complex interactions between gene expression (TRI genes), environmental factors and mycotoxin production. This is a powerful tool for understanding the role of these genes in relation to environmental factors and enables more effective targeted control strategies to be developed.
Keywords: environmental factors temperature trichothecene genes microarray deoxynivalenol multiple regression analyses aspergillus-parasiticus biosynthesis genes water activity wheat-grain growth temperature trichothecenes graminearum ochratoxin expression